2011
DOI: 10.1038/aps.2011.51
|View full text |Cite
|
Sign up to set email alerts
|

Vasorelaxant and antihypertensive effects of formononetin through endothelium-dependent and -independent mechanisms

Abstract: Aim: To investigate the mechanisms underlying the vasorelaxant effect of formononetin, an O-methylated isoflavone, in isolated arteries, and its antihypertensive activity in vivo. Methods: Arterial rings of superior mesenteric arteries, renal arteries, cerebral basilar arteries, coronary arteries and abdominal aortas were prepared from SD rats. Isometric tension of the arterial rings was recorded using a myograph system. Arterial pressure was measured using tail-cuff method in spontaneously hypertensive rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 43 publications
3
38
0
1
Order By: Relevance
“…BBR has been reported to have multi pharmacological effects such as antibacterial effect [19], hypotensive effect [33], and antiviral activity [21, 22]. It has been reported that BBR could regulate signaling pathway in vitro, such as, EGFR/MEK/ERK signaling pathway [23], AMPK/mTOR signaling pathway [24].…”
Section: Discussionmentioning
confidence: 99%
“…BBR has been reported to have multi pharmacological effects such as antibacterial effect [19], hypotensive effect [33], and antiviral activity [21, 22]. It has been reported that BBR could regulate signaling pathway in vitro, such as, EGFR/MEK/ERK signaling pathway [23], AMPK/mTOR signaling pathway [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, here in rat mesenteric arteries we observed that calycosin-elicited relaxation is both endothelium-dependent and endothelium-independent. For formononetin, results from previous studies in rat aortic rings showed that formononetin elicited relaxation through endothelium-dependent pathway involving NO synthesis, and endothelium-independent involving iberiotoxin- (IbTX-) sensitive BK Ca channel, glibenclamide-sensitive K ATP channel, and the inhibition of VDCC [5, 6, 36]. Here in rat mesenteric arteries, we observed very similar effects of formononetin, but in our preparation the sensitivity to IbTX was only observed in endothelium-intact vessels, indicating a more important role of endothelial BK Ca channels in the mesenteric resistance arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that calycosin and formononetin produced antihypertensive effects and improved endothelial and cardiovascular functions [36]. They have been shown to display vasoactive effects in various vascular beds [3, 57]. In rat aorta, calycosin induced vasodilation mainly by inhibiting voltage-dependent Ca 2+ channel (VDCC) in vascular smooth muscle [7], while formononetin caused vasodilation by releasing nitric oxide (NO) in endothelial cells, as well as by the activation of large-conductance Ca 2+ -activated K + (BK Ca ) and ATP-sensitive potassium (K ATP ) channels in aortic smooth muscle cells [6].…”
Section: Introductionmentioning
confidence: 99%
“…We tested the possibility that the mechanism of action of (-)-epicatechin is linked to the inhibition of intracellular Ca 2 þ release mechanisms from the sarcoplasmic reticulum and/or the stimulation of the intracellular Ca 2 þ uptake by the sarcoplasmic reticulum via Ca 2 þ -ATPase. Because the release of intracellular Ca 2 þ is mainly regulated by inositol-trisphosphate receptor system and ryanodine receptor system (Sun et al, 2011), we have investigated the effect of (-)-epicatechin on phenylephrine-and caffeine-induced contractions in Ca 2 þ -free Krebs solution. In this condition, when extracellular Ca 2 þ is absent, contraction to phenylephrine relies on the release of intracellular Ca 2 þ stored in the sarcoplasmic reticulum via activation of the inositol-trisphosphate cascade (Ford and Broadley, 1999;Han et al, 1987).…”
Section: Discussionmentioning
confidence: 99%